Peace and Friendship on the Sipekne’katik: Treaty as a Transformational Practice in the Resistance against Alton Gas - Beaton, Sadie; Eaton, Emily; Paul, Michelle; Tress, Robin (ACME, 2026)
Drawing on the successes of the Mi’kmaq-led struggle against the Alton Gas natural gas storage project from 2014-21, this paper proposes the Peace and Friendship Treaties as the relational framework best equipped to address the worsening climate crisis and build liveable futures in Mi’kma’ki. We argue that existing government and social movement approaches have been unable to adequately arrest climate pollution, and often work to reinscribe the settler-colonial land relations at the heart of intersecting socio-ecological crises. The Treaty Truckhouse movement, which emerged from the successful resistance to Alton Gas, however, builds a resurgent geography capable of addressing both climate change and settler-colonialism in the way that it holds Mi’kmaw and settlers together in evolving relations of care that embrace relational responsibilities to the lands, waters, and climate. The paper draws on both research interviews with people involved in climate action in Mi’kma’ki and on the authors’ own involvement with the movement.